2015
DOI: 10.1080/21645515.2015.1032487
|View full text |Cite
|
Sign up to set email alerts
|

Coverage of the expanded program on immunization in Vietnam: Results from 2 cluster surveys and routine reports

Abstract: . By comparing both cluster survey studies with each other, as well as with routinely collected data, we aim to improve future evaluation of the vaccination coverage in Vietnam and deduce recommendations for the immunization program. According to both methods, the national targets were reached for most of the vaccines: over 90% of children are fully immunized by 1 y of age, 80% Tetanus Toxoid 2 Plus (TT2C) coverage is reached for pregnant women, and 90% TT2C for childbearing aged women. The cluster surveys ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 4 publications
1
13
2
Order By: Relevance
“…For instance, we found that women aged 29-35 years old were associated with increased chances of receiving adequate doses of TT immunization compared to those aged 15-19 years. Similarly, evidence from Ethiopia, Ivory Coast and Turkey support our findings and have reported that women with advancing age were more likely to receive TT protective dose immunization than their counterpart [20,[30][31][32]. A possible reason for this could be that women with advanced age are more matured and might have had past exposure to knowledge about immunization and its benefits for themselves and their children.…”
Section: Discussionsupporting
confidence: 85%
“…For instance, we found that women aged 29-35 years old were associated with increased chances of receiving adequate doses of TT immunization compared to those aged 15-19 years. Similarly, evidence from Ethiopia, Ivory Coast and Turkey support our findings and have reported that women with advancing age were more likely to receive TT protective dose immunization than their counterpart [20,[30][31][32]. A possible reason for this could be that women with advanced age are more matured and might have had past exposure to knowledge about immunization and its benefits for themselves and their children.…”
Section: Discussionsupporting
confidence: 85%
“…The full immunization coverage rates for the three birth cohorts in this study are higher than the 75% rate found in a 2009 study in Ben Tre (3). Results of our evaluation provide evidence of the significant impact of ImmReg on improving immunization coverage.…”
Section: Discussioncontrasting
confidence: 44%
“…Table 1 shows the national immunization schedule for Vietnam from 2010 to 2017 for children under one year old. For better monitoring of the timeliness of EPI vaccination, a registration and reporting system is needed that can efficiently manage the due dates for vaccination of children and report the most accurate figure of full immunization coverage (3).…”
Section: Introductionmentioning
confidence: 99%
“…24 After implementation of EPI, Vietnam has achieved many vaccine-related milestones, such as becoming polio-free in 2000 and eliminating maternal and neonatal tetanus in 2005. 25 , 26 A recent estimate by the World Health Organization indicated that 96% of the population is covered by the diphtheria-tetanus-pertussis vaccine; and that 99% of the population received the first measles vaccine, with 95% of the population receiving the second dose. 27 However, these successes have been threatened by the media’s reporting of Adverse Events Following Immunization (AEFIs), 19 which refers to “any untoward medical occurrence which follows immunization and which does not necessarily have a causal relationship with the usage of the vaccines”.…”
Section: Introductionmentioning
confidence: 99%